Education Opportunities for Librarian as Educator: the Case of Lithuania - Grigas, Vincas (Information & Media, 2011)
The article discusses whether the study programmes aimed at preparing professional librarians produce the entirety of competencies necessary for librarians as educators. The research aims to evaluate how the study curricula such as informology (Klaipėda University), library information resources management (Šiauliai State College), library and information studies (Vilnius University) are relevant to the professional standards of librarians as educators. For the research were used the standards for Proficiencies for Instruction librarians and coordinators prepared by the Association of College and Research Libraries. For data analysis factor analysis was used. The research proved that the Standards for Proficiencies for Instruction Librarians and Coordinators and factor analysis may be an appropriate method for the assessment of the study programmes designed for preparing future professional librarians, i.e., in evaluating whether the competencies developed under the study programme correspond to the entirety of the competencies peculiar to librarians as educators. The study findings suggest that study programmes such as informology, Library and information science, and library information resources management meet most of the standards criteria. The Vilnius University study programme meets them best.